Reason, Rationality, and Fiduciary Duty - Lydenberg, Steve (Journal of business ethics, 2014)
This paper argues that since the last decades of the twentieth century the discipline of modern finance has directed fiduciaries to act "rationally"—that is, in the sole financial interest of their funds--downplaying the effects of their investments on others. This approach has deemphasized a previous, more "reasonable" interpretation of fiduciary duty that drew on a conception of prudence characterized by wisdom, discretion and intelligence—one that accounts to a greater degree for the relationship between one's investments and their effects on others in the world. The reasonable approach allows fiduciaries to a greater degree to assess the objective well-being of beneficiaries, to recognize fundamental sources of investment reward in the economy, and to fulfill their obligations to allocate benefits impartially between current and future generations. Reason and rationality can work in a complementary fashion to make investment long-term in its perspective and beneficial to society and the economy as well as to specific funds or portfolios. Determining how to accomplish this challenging task is part of the obligation of fiduciaries as they seek to realize the full potential of the investment assets entrusted to their care.